MOTOR CONTROL FOR GAIT IN CASES OF IDIOPATHIC TOE WALKING - Salsabila, Savira Rizka Meidy; Rahayu, Umi Budi (Academic Physiotherapy Conference Proceeding, 2021)
This case report shows a motor control exercise program as a treatment for walking patterns in children with idiopathic tip toe walking. A 5 year old child with talipes equiness walking pattern, during treatment received motor control with stair-step standing, standing balance, stooping and transition activities, control stepping, sensory and intrinsic foot activities, age-appropriate motivation method, information for parents, and home activities to facilitate a more upright standing and walking posture to strengthen surface reaction forces relative to the ankle axis. This program is conducted for 1 hour per session twice a week. Prior to intervention the patient had a Functional Gait Assessment (FGA) score of 8 with the highest score of 30. After 2 weeks of treatment, the Functional Gait Assessment (FGA) score increased by 17 with the highest score of 30. Our results suggest that a functional rehabilitation program may be beneficial in functional recovery. walking patients with idiopathic tip toe walking in children.